DISRUPSI TEKNOLOGI VERSUS ADAPTASI: GELIAT GRUP MUSIK NASIDA RIA DI ERA KIWARI (KAJIAN ARKEOLOGI MEDIA) - Khothibul Umam; Laura Andri Retno Martini (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
Technological disruption is a necessity in all fields. With its massive development, technology has succeeded in reformulating the pattern of production, distribution, and consumption of a work of art, and music is no exception. This is what happened to Nasida Ria. Since their establishment in 1975, they have continued to create works without stopping with various adaptations according to the technology of the era. The use of new media such as the internet, social media, and digital music services is really useful to continue to make Nasida Ria relevant in the current era. This study takes the object of Nasida Ria and their adaptation to technological disruption. The method used in this research is descriptive qualitative method. The research data was obtained by studying literature and documents. The documents we examined were various forms of Nasida Ria's digital releases, especially those on the Spotify platform. The analytical method used in this study is to examine the extent to which Nasida Ria adapts in the era of technological disruption to the theory of Media Archeology. The result of her research is that it is proven that Nasida Ria can adapt to technological disruptions that occur in the Indonesian music world.